Scavengers use natural and anthropogenic resources connecting protected areas with surrounding lands - Ho, Cameron; Marzluff, John M.; Stahler, Daniel R.; Smith, Douglas W.; Mueller, Thomas; Wikelski, Martin; Safi, Kamran; Loretto, Matthias-Claudio (Frontiers in Bird Science, 2023)
Anthropogenic food subsidies can alter ecosystem processes such as competition, predation, or nutrient transfer and may strongly affect protected areas. Increasing recreation and ecotourism often create food subsidies, especially in the surrounding lands through fast-growing gateway communities. How the effects of these subsidies extend into protected areas when animals move across boundaries remains largely unexplored. We addressed this question by studying the movement and foraging of common ravens (Corvus corax), opportunistic scavengers well known to feed on predator kills as well as on anthropogenic food subsidies. We analyzed spatiotemporal data from 57 GPS-tagged ravens, trapped within or close to Yellowstone National Park, to study their seasonal use of natural and anthropogenic food sources. Although Yellowstone National Park contains a full suite of native predators where ravens can be observed at virtually every kill site, we show that anthropogenic subsidies were utilized to a much greater extent than other natural resources, especially during winter. Important subsidies included gutpiles of harvested game animals left by hunters, fat present on waste water settling ponds, roadkill, and waste from agricultural and urban activities. These subsidies were distributed over vast areas beyond Yellowstone National Park. During fall/winter, ravens traveled longer distances (21.9 km vs 13 km) and spent more time outside of the National Park (73% of GPS points outside), mostly feeding on anthropogenic subsidies, compared to spring/summer (42% of GPS points outside). This difference between seasons was more pronounced for individuals holding territories within the protected area than for those without territories. The large area over which ravens used anthropogenic food subsidies (within 100 km of Yellowstone National Park) affects the park’s raven population and the scavenging services they provide. We suggest that the scale of resource use must be considered by managers seeking to control expanding raven populations elsewhere.